FAKTOR – FAKTOR PENENTU WAKTU, AKSESIBILITAS, BIAYATRANSPORT, PENDAPATAN TERHADAP PENGGUNAAN JASA TRANSPORTASI TRANSKOETARADJA KOTA BANDA ACEH (STUDI KASUS: KORIDOR I KEUDAH – DARUSSALAM 2018/2019) - Lukmana Yushar; Fakhruddin Fakhruddin (Fakultas Ekonomi dan Bisnis UNSYIAH, 2019)
AbstrackWith the availability of public transportation, it is one of the alternatives to overcome congestion problems that often occur in every region. Public transportation provided by the government is intended to facilitate the public in carrying out routine activities carried out every day. The problems that occur are what factors cause the people of Banda Aceh City to be reluctant to use Trans Koetaradja. So in this study using variables, time, accessibility, transport costs and income. For the method using descriptive method which conducts a field survey to see the results of the research. The results of the discussion of this study indicate that time and income variables show significant results, while accessibility and transport costs are not significant.Keywords: Time, Accessibility, Transport Costs, Revenue